Immunogenicity and safety of a proposed pegfilgrastim biosimilar MSB11455 versus the reference pegfilgrastim Neulasta® in healthy subjects: A randomized, double‐blind trial. Issue 2 (25th April 2020) - Wynne, Chris; Schwabe, Christian; Vincent, Emmanuelle; Schueler, Armin; Ryding, Janka; Ullmann, Martin; Ghori, Vishal; Kanceva, Radmila; Stahl, Michael
Abstract: MSB11455 is a proposed biosimilar to the currently licensed reference pegfilgrastim (Neulasta ® ). This study was designed primarily to compare the immunogenicity of MSB11455 and Neulasta ® . As secondary objectives, the safety and tolerability of MSB11455 and Neulasta ® were also compared. Healthy adult subjects were randomized to either MSB11455 or Neulasta ®, stratified by antipolyethylene glycol (PEG) antibody status at screening and study site. Subjects received a single subcutaneous dose of MSB11455 or Neulasta ® (both 6 mg/0.6 mL) on day 1 of each of two study periods (same product in both periods), separated by a washout of 28‐35 days. Immunogenicity samples were taken predose and up to day 84 post–first dose. Noninferiority was confirmed if the upper limit of the exact one‐sided adjusted 95% confidence interval (CI) for the difference in antidrug antibody (ADA)‐positive rates was < 10%. Safety was assessed throughout the study. Overall, 336 subjects were randomized and treated (N = 168 in each group). Noninferiority of MSB11455 over Neulasta ® was demonstrated for immunogenicity; the difference in confirmed treatment‐induced ADA‐positive rate between MSB11455 and Neulasta ® was −0.6% (upper limit of the exact one‐sided adjusted 95% CI: 6.25%). ADAs were mostly directed against the PEG moiety of pegfilgrastim. No filgrastim‐specific neutralizing antibodies were detected in either treatment group. Safety and tolerability were as expected for pegfilgrastim, and comparable between treatments. This study supports and strengthens the available evidence for the biosimilarity of MSB11455 to Neulasta ® .